Growth of branches of petung bamboo (Dendrocalamus asper) grafting in soil media, husk charcoal, and their combination - Adriana Adriana; Widaryanti W. Winarni; Daryono Prehaten; Ganis Nawangsih (Jurnal Ilmu Kehutanan)
Recently, the utilization of bamboo is more extensive, but the attention towards its regeneration is not sufficient. The use of stem or branch cuttings are more practical and having more benefits and promising because the cutting materials are more available, easier to gain, cheaper, undamaging the source clump, faster in the taking time, and easier in the clump formation. The common rooting media used is top soil (the fertile part of upper layer soil). Recently, it is quite hard to provide top soil in a large number. Thus, it is important to find an alternative source in order to decrease the use of top soil that is by mixing the top soil media with other materials. The media used were soil media, husk charcoal, and the mixture of soil and husk charcoal (2:1). The branch cuttings used were branches of petung bamboo taken from 2 years old amboo, with 2-3 cm in diameter, and 2 nodus in length. The treatment was done by giving some variations in the soil media, the husk charcoal,and the mixture of soil and huskcharcoal. The mixture of soil and huskcharcoal media gave a significant influencet o the length of sprout variable,but it did not give significant influence to the number of sprout, the length of root, and the percentage of rooting.